Cone dysfunctions in retinitis pigmentosa with retinal nerve fiber layer thickening - Sobaci G (Dove Medical Press, 2012)
Güngör Sobaci, Gökhan Özge, Fatih Ç GündoğanDepartment of Ophthalmology, Gülhane Military Medical Academy and Medical School, Etlik, Ankara, TurkeyPurpose: To investigate whether or not thicker retinal nerve fiber layer (RNFL) in retinitis pigmentosa (RP) patients relates to functional abnormalities of the photoreceptors.Methods: Optical coherence tomography-based RNFL thickness was measured by Stratus-3™ (Zeiss, Basel, Switzerland) optical coherence tomography and electroretinogram (ERG) recordings made using the RETI-port® system (Roland, Wiesbaden, Germany) in 27 patients with retinitis pigmentosa and in 30 healthy subjects.Results: Photopic ERG b-wave amplitude, cone ERG b-wave latency, 30 Hz flicker amplitude, and 30 Hz flicker latency had significant correlations to the RNFL-temporal (r = —0.55, P = 0.004, r = 0.68, P = 0.001, r = —0.65, P = 0.001, and r = —0.52, P = 0.007, respectively). Eyes with thicker RNFL (ten eyes) differed significantly from those with thinner RNFL (eight eyes) regarding cone ERG b-wave latency values only (P = 0.001). Conclusion: Thicker RNFL in patients with retinitis pigmentosa may be associated with functional abnormality of the cone system.Keywords: optical coherence tomography, electroretinography, photoreceptor, b-wave